1998
DOI: 10.1097/00001756-199802160-00012
|View full text |Cite
|
Sign up to set email alerts
|

Stages of estrous mediate the stress-induced impairment of associative learning in the female rat

Abstract: Exposure to a stressful event facilitates classical eyeblink conditioning in male rats and impairs conditioning in females. The contribution of stages of estrous to the stress-induced impairment of eyeblink conditioning was evaluated. Females in proestrus, estrus and diestrus were either exposed to an acute stressor of intermittent tailshocks or swim stress and compared to unstressed females in the three stages. Females in proestrus, when estrogen levels are high, acquired the conditioned response at a facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 13 publications
8
97
1
1
Order By: Relevance
“…1B) (Shors et al, 2000 for review;Shors, 2000Shors, , 1998Beylin and Shors, 1998;Servatius and Shors, 1994;Shors et al, 1992). In contrast, exposure to the very same stressor dramatically impaired conditioning in females (Wood and Shors, 1998;Shors et al, 1998;Wood et al, 2000) (Fig. 1A and 1B).…”
Section: A Stress-induced Performance Deficit In the Female Ratmentioning
confidence: 93%
“…1B) (Shors et al, 2000 for review;Shors, 2000Shors, , 1998Beylin and Shors, 1998;Servatius and Shors, 1994;Shors et al, 1992). In contrast, exposure to the very same stressor dramatically impaired conditioning in females (Wood and Shors, 1998;Shors et al, 1998;Wood et al, 2000) (Fig. 1A and 1B).…”
Section: A Stress-induced Performance Deficit In the Female Ratmentioning
confidence: 93%
“…It has also been demonstrated that the most severe stress-induced impairment occurred during proestrus, the estrus phase in which estrogen levels are highest. 32 In contrast, estrogen appears to facilitate spatial processing during stress 29 , indicating that estrogen's role in the stress response likely varies throughout the brain, enhancing function in some areas, while debilitating others.…”
Section: Estrogen Influences On Non-pfc Functions During Stressmentioning
confidence: 99%
“…More recent in vitro studies have demonstrated that the estradiolinduced increase in spine density increases the sensitivity of the cells to N-methyl-Daspartate receptor-mediated synaptic input (28). There are a number of studies suggesting that learning ability varies over the course of the estrous cycle in female rats (29)(30)(31)(32)(33), although several other studies have not found any changes (34,35). In addition, estrogen replacement therapy appears to preserve memory function in post-menopausal women (36,37), as well as in ovariectomized female rats (38).…”
Section: Role Of Hormones In Brain Development and Cognitionmentioning
confidence: 99%